State of the art of cervical cancer treatment in rare histologies - Arango-Bravo, Eder Alexandro; Galicia-Carmona, Tatiana; Cetina-Pérez, Lucely; Flores-de la Torre, Celia Beatriz; Enríquez-Aceves, María Isabel; García-Pacheco, José Antonio; Gómez-García, Eva María (Frontiers in Oncology, 2024)
The objective of this review is to summarize the current scientific evidence to formulate clinical recommendations regarding the classification, diagnostic approach, and treatment of rare histological subtypes of cervical cancer; neuroendocrine carcinoma, gastric-type mucinous adenocarcinoma, and glassy cell adenocarcinoma. These histological subtypes are generally characterized by their low frequency, aggressive biological behavior, certain chemoradioresistance, and consequently, high recurrence rates with a deleterious impact on survival. Molecular studies have identified several associated mutations in neuroendocrine carcinoma (PIK3CA, MYC, TP53, PTEN, ARID1A, KRAS, BRCA2) and gastric-type adenocarcinoma (KRAS, ARID1A, PTEN) that may serve as molecular targets. While adenocarcinomas are typically treated and classified based on squamous histology across early, locally advanced, and advanced stages, the treatment strategies for neuroendocrine carcinomas in early stages or locally advanced cases differ, particularly in the sequencing of administering chemotherapy, chemoradiotherapy, or surgery. The chemotherapy regimen is based on etoposide plus cisplatin (EP). Unlike squamous cell carcinomas, immune checkpoint inhibitors are yet to establish a standard role in the treatment of recurrent neuroendocrine carcinomas due to the absence of clinical trials. Regarding glassy cell adenocarcinomas and gastric-type adenocarcinoma, the potential use of immunotherapy in advanced stages/disease requires further evaluation through international collaborations, given the limited number of cases.